2015
DOI: 10.5551/jat.28381
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Fat Thickness is Increased in Vitamin D Deficient Premenopausal Women and does not Decrease after Short-term Replacement

Abstract: Aim: Vitamin D deficiency, which is prevalent among young women in Middle Eastern populations, has been linked to cardiovascular disease. Epicardial adipose tissue (EAT) has also been found to be associated with coronary artery disease. However, data on the relationship between vitamin D status and epicardial adiposity is limited. This study aims to investigate the effect of vitamin D deficiency and replacement therapy on EAT thickness in healthy, young premenopausal women. Methods: Thirty-one premenopausal wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Indeed, several epidemiological studies have shown that impaired vitamin D status was associated with increased risks of different chronic diseases including CVD and diabetes [ 70 ]. The results of the present study are following what has already been published by others [ 71 ], showing significant differences between 25(OH)D levels and EF quartiles; indeed, as EF thickness increased, 25(OH)D levels decreased. Besides, a negative and significant correlation between EF and vitamin D levels in the female and total population was observed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, several epidemiological studies have shown that impaired vitamin D status was associated with increased risks of different chronic diseases including CVD and diabetes [ 70 ]. The results of the present study are following what has already been published by others [ 71 ], showing significant differences between 25(OH)D levels and EF quartiles; indeed, as EF thickness increased, 25(OH)D levels decreased. Besides, a negative and significant correlation between EF and vitamin D levels in the female and total population was observed.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, long periods of vitamin D replacement therapy might be particularly useful in older women with increased risk for CVD, recommending long follow-up to demonstrate the potential beneficial effects of vitamin D replacement on epicardial adiposity. It is noteworthy that even if EF has been proven to contribute to inflammation by pro-inflammatory cytokine discharge, and investigations have been performed on vitamin D receptors in different tissues, including the epicardial one [ 71 ], no strong evidence of the generalized inverse relationship between vitamin D and EF were obtained and further studies are needed to better elucidate the molecular mechanisms [ 74 ]. Finally, in the present study, an inverse and significant correlation was found between 25(OH)D and glucose levels in females and the total population, suggesting how reduced levels of vitamin D could impair pancreatic β-cell functions, thus compromising insulin secretion [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…These indicators are inversely related to 25(OH)D in non-obese T2D patients in our study ( Table 2 ). A growing body of evidence demonstrates that vitamin D deficiency is involved in EATT and inflammatory response in premenopausal women and patients with coronary artery disease or metabolic syndrome [ 12 , 13 , 26 ]. In our study, increased EATT, which indicates visceral obesity, was associated with decreased 25(OH)D levels by correlation analysis ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing attention should be paid to the potential role of vitamin D in inhibiting adipogenic transcription factors and preventing excess lipid accumulation, adipocyte hypertrophy, and subsequent inflammation [ 10 , 11 ]. Several clinical studies have shown that the EAT thickness (EATT) was inversely correlated with 25-hydroxyvitamin D [25(OH)D, Calcifediol] level, which is considered the best marker for whole-body vitamin D status [ 12 , 13 ]. However, it remains unclear whether circulating 25(OH)D levels are correlated with EATT in normal-weight type 2 diabetes (T2D) patients.…”
Section: Introductionmentioning
confidence: 99%